The origin and development of the liturgy in Geneva under Calvin to the present day with special reference to the Sunday morning service and Holy communion and their doctrinal significance - Kaltenrieder, André E (Rhodes University, Faculty of Divinity, Department of Divinity, 1961)
The first section of this chapter sets out the rise of civil government in Geneva and how the stage was set for the take-over of ecclesiastical authority by the civil powers. The second section outlines the growing discontent of the Genevans with episcopal authority since their bishop had become dangerously favourable to the house of Savoy. Farel's forceful preaching drew many sympathisers and these, added to those who sought political freedom, soon found themselves in a position to proclaim the Reformation of Geneva. Chapter II: In this chapter, we examine the structure of the Church in the later middle ages. The examination of a sixteenth century Missal sets the norm by which Reformation liturgies may be judged. Chapter III: Will attempt to date Farel's Maniero et Fasson is made in the light of his reforming activities. The origin of his thought is traced to Lefèvre d'Etaples. This thought is brought out in the liturgy which must be considered as the first Genevan reformed liturgy. Chapter IV The origins of Calvin's liturgy are to be found in Strasburg. Diebold Schwartz was the first to translate the Mass into German, reforming its contents, and is found to have been the first to celebrate this German Mass in Strasburg. This Mass is examined for the tendencies which it represents of a break away from many of the more blatant distortions of late Medieval worship. Bucer's ascendency at Strasburg is outlined because of the changes which he brought about in the liturgy. Chapter V: Calvin' s Strasburg liturgy is examined in relation to Bucer's and its distinguishing tendencies are brought to light. The rise of the first French Psalter, and the origin of its tunes is taken into account. Calvin's return to Geneva resulted in the publication of another liturgy derived from that of Strasburg, but this liturgy did not fulfil Calvin's aspirations for it was limited by the prevailing religious opinion which Calvin was forced to take into account. As against this, Calvin's ideal of worship is exanined, as well as the place given by Geneva to the adherence to the Christian Year. Chapter VI: The eighteenth century in Geneva witnessed the rise of rationalism and the rejection of the oversystemtised Calvinisn which followed the Reformer's death. But at the same time, the prevalent ecumenical concern brought about a new consciousness of the traditional forms of worship. The effect of these two currents of thought is traced in the 1724 Genevan liturgy. Chapter VII: In the nineteenth century we are faced with a more thoroughgoing rationalism, with revivalist pietism and with a new spirit of liberalism which has sprung out of the changing political outlook. These elements are expressed in the liturgies of the time. When the 1875 liturgy was drawn up, liberal opinion had gained such a strong hold that a dual liturgy was deemed necessary, in which alternative forms were prescribed for those who disagreed with the orthodox doctrines. The separation of Church and State government resulted in a revision of the liturgy. But the only exanple of this thought is contained in the forms for the morning service published in 1921. Chapter VIII: The liturgy of the twentieth century is a witness to the vitality of the movement towards liturgical renewal. But it appears to lack solid doctrinal foundation in the multitude of texts provided to cater for all ranges of opinion. Nevertheless, it contains many traditional elements as well as a number of reformation forms, though the latter are usually presented as they appeared in the seventeenth century revision. This liturgy, therefore, is a sign that a new consciousness of worship has entered the Genrvan Church and bears, within it, the promise of possible further developments. C0NCLUSION: In conclusion, we take note of the movements which have influenced the liturgy throughout this study, finding that with the exception of Calvin, there has never been a proper theological approach to thi liturgy. It is just such a theological approach that is necessary if the Genevan liturgy is to reap the benefits of the present air of liturgical renewal. Summary, p. ii-iii.
Keywords: Liturgics; Reformed Church -- Liturgy; Reformation -- Switzerland